A classical delphi study to identify the barriers of green information technologies - Gotay, Jose A. (Open Science Journal, 2020)
This qualitative, classical Delphi study explored the apparent lack of corporate commitment to prioritized Green Information Technologies (GITs), which could delay the economic benefits for maximizing the use of energy resources. The purpose of this study was to examine the leadership barriers impeding the adoption of GITs. A panel of nineteen Information Technology and Sustainability experts participated in this study. The panels' members were from industry, government, and academia. The NVivo 9 software was used for the qualitative data analysis and reports the results. The leadership barriers identified in this study as impeding were the lack of understating of GIT and the benefits it can yield for organizations. To gain energy cost reductions, and to meet future environmental regulations, a paradigm change is needed to integrate GIT into organizational strategies, processes, and culture. The results of this study give useful recommendations to rationalize the adoption of GIT to overcome implementation barriers.